(untitled) (Kénosis, 2020)
A neural network supposes a learning that the present work set out to reveal as asymmetries between narratives of sexist violence. A retrospective, descriptive and interpretive study was carried out with an intentional selection of students in a public Institution of Higher Education (IES) in central Mexico. A contemplative structure was revealed, considering the synaptic weights that explained the relationship between the entry, processing and exit of units of idealization, contemplation and conflict planning. Research lines related to the structure of relationships between the categories are suggested.